The Routledge companion to big history
1 online resource
Keywords: "The Routledge Companion to Big History guides readers though the variety of themes and concepts that structure contemporary scholarship in the field of big history. The book is divided into five parts, each representing current and evolving areas of interest to the community, including big history's relationship to science, social science, the humanities, and the future, as well as teaching big history and 'little big histories'. A timely collection with contributions from leading proponents in the field, it is the ideal guide for those wanting to engage with the theories and concepts behind big history"--